PENATAAN KAWASAN PELABUHAN RASAU JAYA KABUPATEN KUBU RAYA - Almaida, Tia; Muazir, Syaiful; Pebriano, Valentinus (JMARS: Jurnal Mosaik Arsitektur, 2022)
The Rasau Jaya Port area is a port area located in Kubu Raya Regency which serves shipping routes to the hinterland of West Kalimantan. The journey taken is a cross route within Kubu Raya Regency and a cross route between districts, namely North Kayong Regency. However, judging from the area and the port service office, this is still not feasible for an inter-district port area. Therefore, the Rasau Jaya Port area requires an area arrangement according to existing regulatory standards. The design methodology is adopted in stages, namely ideas, data collection, analysis, synthesis and design. With an area design concept that refers to the functions and standards of ferry port requirements. This can make the port a more organized area like a port in general.